Model Pengukuran Working Out Loud (WOL) Terhadap Adopsi Enterprise Social Networks (ESNs) - Enggar Sulistiyono; Endang Kustami (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2023)
This study aims to examine the concept of Working Out Loud (WOL) in measuring the success rate of implementing Enterprise Social Networks (ESNs) in companies. The adoption of this technology has not been widely implemented by companies in Indonesia. Implementing ESNs in companies as a tool to drive increased employee collaboration requires integration of social media and enterprise technology infrastructure. This platform does provide benefits for companies in the areas of innovation, increased productivity, and also employee engagement; but on the other hand there are several failures caused by employee factors that only focus on implementing technology without changing employee behavior patterns and also how to measure this behavior. The concept of Working Out Load (WOL) is an indicator tool that can be used to measure the success of ESNs implementation. Although the concept of WOL is still unclear, it provides many benefits. Not much research has discussed the benefits that exist in this relationship. The initial hypothesis of this study is that the two behavioral factors above exist and influence each other but are different, so measurements can be made with the developed scale. This study uses a survey distributed to employees of PT. Djarum (one of the large companies in Indonesia) which has implemented ESNs technology in the period October - November 2022. Processing exploratory analysis and data confirmation using SPSS 22 and AMOS 22 with a total of 313 respondents; which was divided randomly with 200 respondents for confirmation analysis and the rest as data for exploratory analysis. Departing from the abnormal nature and ordinal nature of the item scale used, this study uses the Spearman method (not Pearson). This aims to confirm the hypothesis so as to produce a rating scale for individuals and groups of WOL, so that researchers and practitioners can find WOL behavior in a company as a continuous process. The results of this study can be used as a reference for companies in Indonesia to develop ESN technology and measure the success rate of their operations.